Adlerian counseling, fear of intimacy, and social interest among university students - Alkhazaleh, Ziad M.; Alkhawaldeh, Mohammad K.; Mhaidat, Fatin A. (Institute of Advanced Engineering and Science, 2024)
University students in early adulthood indeed encounter diverse developmental demands, particularly in the realm of relationships and social development. This stage often involves considerations related to establishing families and entering into marriage or long-term partnerships. This study aims to assess the efficacy of a premarital counseling program grounded in the Adlerian approach in enhancing intimacy and social interest among a sample of single university students. The sample comprised 718 single young individuals from a public university in Jordan. Among them, 38 students displaying low social interest and experiencing fear of intimacy voluntarily participated. They were divided into two groups: an experimental group of 19 participants and a control group of 19 participants. The study utilized two measurement scales-one for fear of intimacy and another for social interest. The group counseling program, consisting of 11 sessions, was administered. The findings revealed significant differences between the experimental and control groups in pre- and post-measurements, indicating the positive impact of the group counseling program on the experimental group. Additionally, follow-up assessments indicated that the beneficial effects of the group counseling program were sustained over time.